Dating violence in a sample of Colombian students: relation with gender-based violence in the near context - Bonilla-Algovia, Enrique (2019)
Background: Socializing processes taking place in a violent environment may cause a subsequent acquisition and acceptance of violent behaviors. The main aim of this research is to analyses the association between gender-based violence in the near context and the perpetration and victimization of dating violence. Method: The study sample consists of 443 students from different Colombian universities, and their mean age is 20.64 years old (SD = 3.91). The levels of aggression were measured by the modified version of the Conflict Tactics Scale (M-CTS). Results: The situations of gender-based violence in the near context are associated to perpetration and victimization of dating violence. Conclusion: The exposure to gender-based violence may influence the normalization of violence and its emergence in dating relationships. It might be necessary to take into account this association, in order to include it in prevention and awareness plans.